Effectiveness of Artocarpus altilis (Parkinson ex F.A.Zorn) Fosberg ethanol extract in suppressing inflammation and cartilage degeneration in animal models of osteoarthritis - Fitrya; Muharni; Fatma Sri Wahyuni; Annisa Amriani (GarVal Editorial Ltda., 2024)
Context: Osteoarthritis (OA) is a degenerative joint disease characterized by an inflammatory reaction and cartilage degradation. Artocarpus altilis is a well-known traditional medicine with various phenolic and flavonoid content. Several pharmacological properties of A. altilis extract (AAE) have been reported, but its effectiveness in osteoarthritis is unknown. Aims: To investigate the potential of AAE as an anti-osteoarthritis. Methods: The Wistar rats induced OA with mono-iodoacetate (MIA). The OA model rats were treated with AAE with three dose levels (100, 200, and 400 mg/kg) for 28 days. As a positive control used Na-diclofenac (20 mg/kg). Serum IL-1β, IL-10, MMP-3, and MMP-13 levels and histopathological profiles were compared to the MIA group and normal control (5% Na-CMC). Results: The experimental results showed that AAE could significantly suppress the production of inflammatory mediator factor IL-1β, matrix-degrading proteinase MMP-3, MMP-13, and cartilage degeneration. In addition, AAE increased the production of the anti-inflammatory mediator IL-10, improved synovial inflammation, and increased cartilage thickness. Conclusions: A. altilis extract has the potential to be developed as an anti-osteoarthritis therapeutic agent from natural medicine.